The Stumbling Block of Net Profit Margin: A Case Study of PT PLN Batubara - Willya Hendra; Mangkusubroto, Kuntoro (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
PT PLN Batubara is a subsidiary of PT PLN (Persero), which has the role of Security of Supply for PLTU and Contributing to cost efficiency. The company shows a positive trend about securing business sustainability by an upward trend of coal delivery year by year. However, the increase in revenue was not followed by a remarkable increase in profit margin. Based on the last three years of financial statement data, the company never meets the net profit margin target, which has planned on its corporate planning. This research objective is to answer the root cause of this problem, develop possible solutions to improve net profit margin and choose the optimum alternative to be implemented. This research is based on rational decision-making framework combined with internal and external analysis to define factor impacting net profit margin of PT PLN Batubara. This research is conducted using Mixed-Method, both qualitative and quantitative methods. Research shows that there are some internal and external factors that deterrent the increasing of profit margin. Regarding to internal factors, business model which relies on suppliers made the company struggling in controlling the cost production. Furthermore, it is getting worse with the Domestic Market Obligation (DMO) policy. Therefore, in order to address those stumbling factors, the company should optimize supply chain management by looking for an alternative supplier. Keywords: net profit margin, rational decision, decision analysis, coal, potential problem analysis